THE FEATURES OF ANTENNA ARRAY RADIATOR EXCITATION AMPLITUDE RANDOM ERRORS EFFECT - A. P. Joubko; A. A. Popov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Two types of linear antenna array radiator excitation random errors are analyzed. The first type is multiplicative errors, the second type is additive errors. The effect of these two types on average antenna pattern, pattern parameters, random realization parameters is analyzed.